2020
DOI: 10.1017/jfm.2020.588
|View full text |Cite
|
Sign up to set email alerts
|

Temporal dynamics of large-scale structures for turbulent Rayleigh–Bénard convection in a moderate aspect-ratio cylinder

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…This rough characterization of the flow structure is consistent with the distributions of the vertical velocity component in figures 5(c) and 5(d). The appearance of finer structures in the velocity contours illustrates the character of inertia-dominated fluid turbulence and is in line with previous studies (Pandey et al 2018;Vogt et al 2018a;Krug et al 2020;Sakievich et al 2020) which demonstrated the occurrence of more small-scale velocity fluctuations compared with the temperature field. Thus, it can be stated that the results of the numerical simulations confirm the mean flow structure of the cellular regime suggested from the experiment based on a limited number of velocity sensors (Akashi et al 2019).…”
Section: Experimental Set-upsupporting
confidence: 91%
See 4 more Smart Citations
“…This rough characterization of the flow structure is consistent with the distributions of the vertical velocity component in figures 5(c) and 5(d). The appearance of finer structures in the velocity contours illustrates the character of inertia-dominated fluid turbulence and is in line with previous studies (Pandey et al 2018;Vogt et al 2018a;Krug et al 2020;Sakievich et al 2020) which demonstrated the occurrence of more small-scale velocity fluctuations compared with the temperature field. Thus, it can be stated that the results of the numerical simulations confirm the mean flow structure of the cellular regime suggested from the experiment based on a limited number of velocity sensors (Akashi et al 2019).…”
Section: Experimental Set-upsupporting
confidence: 91%
“…In this general respect, our study is comparable to the work of Sakievich et al (2016Sakievich et al ( , 2020, although the observed flow patterns differ from each other, which we believe is due to the differences in the shape of the convection vessels (cylinder versus box). In particular, it is not surprising that the flow in the box is restricted in its dynamics and does not form a rotational symmetry as shown by Sakievich et al (2020). The cellular flow regime, instead, shows mirror symmetry with respect to the two vertical centre planes x = 2.5 and y = 2.5 of the convection box, respectively.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations